EVOLUSI IDEOLOGI AL-AZARIQAH: DARI EKSTREMISME KLASIK KE RADIKALISME KONTEMPORER - Misnawi; Ishlakhatus Sa’idah; Abbadi Ishomuddin (Almustofa Journal of Islamic Studies and Research, 2025)
Al-Azariqah was the most extreme faction of the Khawarij sect that emerged in the early period of Islam, particularly during the post-Rashidun Caliphate era. This group was known for its violent actions and frequent practice of takfir against Muslims and other groups who did not conform to their beliefs. This article aims to explore the origins of Al-Azariqah, their attitudes and thoughts, and the analysis of their similarities with contemporary radical movement. By using a qualitative method and a historical-critical approach, the study reveals a stark contrast between Al-Azariqah and other Khawarij factions, as well as the ideological legacy they left behind in Islamic thought discourse. Al-Azariqah positioned themselves as a group that claimed exclusive religious purity. They also practiced religious teachings based on their own interests and through a textual and partial understanding of the contents of the Qur'an. This study also emphasizes that the existence of Al-Azariqah represents one of the earliest examples of how religious radicalism can emerge from political tension and crises of authority in Islamic history.